China's economic transformation - Chow, Gregory C., 1929- (Wiley Blackwell, 2015)
Now available in a fully-revised and updated third edition, this established textbook provides a penetrating and comprehensive analysis of the historical, institutional, and theoretical factors that have contributed to China's economic success. Includes coverage of China's foreign investments, trade with regional partners, Chinese human capital, and bureaucratic economic institutions Covers a diverse set of important issues, including environmental restraints, income distribution, rural poverty, the education system, healthcare, exchange rate policies, monetary policies, and financial regulation Accessibly written and intelligently organized to offer a straightforward guide to China's economic evolution Written by a lauded economist, researcher, and advisor to government officials in mainland China and Taiwan.